A factorial design-optimized microfluidic LNP vaccine elicits potent magnesium-adjuvating cancer immunotherapy - Yongyi Xie; Jiaxin Guo; Jialin Hu; Yuan Li; Zhongqian Zhang; Yongcheng Zhu; Fei Deng; Jialong Qi; You Zhou; Wenjie Chen (Materials Today Bio)
Human papillomavirus (HPV)-associated cancers remain a critical health challenge, prompting the development of effective therapeutic vaccines. This study presents a lipid nanoparticle (LNP)-based vaccine co-loading E7 antigen peptide and magnesium ions as the adjuvant. Microfluidic technology was employed to optimize LNP preparation and formulation, ensuring efficient co-delivery of antigen and adjuvant. Magnesium ions were chosen over conventional aluminum-based adjuvants, which often suffer from limited efficacy and adverse effects, particularly for cancer immunotherapy. Compared to aluminum, magnesium ions exhibited superior capabilities in enhancing T-cell activation and promoting cellular immune response. Mechanistic insights suggest that magnesium ions facilitate dendritic cell maturation and antigen presentation via a collagen-CD36 axis, contributing to the adjuvant activity of magnesium. Through design of experiments (DoE) optimization, the LNP formulation was tailored for enhanced encapsulation and stability, positioning it as a targeted system for immune activation. These findings support the promise of magnesium ions as effective and safer adjuvants in LNP-based vaccines, marking a potential advancement for therapeutic cancer vaccination.